Endoscopic Ultrasound-Guided Angiotherapy for Gastric Varices—A Small Retrospective Study - Sharma, Kapil; Sharma, Mamta; Singh, Sanchit (Journal of Digestive Endoscopy, 2020)
Introduction Conventional n-butyl-cyanoacrylate (CYA) recommended for secondary prophylaxis of gastric varices (GV) is associated with significant rebleeding and glue embolism. Limited data are available on more successful and less risky endoscopic ultrasound-guided coils and CYA (EUS-Coils-CYA) injection in GV.Methods We present a retrospective case series of 12 patients with GV bleeding managed successfully with EUS-Coils-CYA injection leading to variceal eradication in 11 patients.Results From January 2018 to June 2019, 12 cases of GV, which were either bleeding or bled recently, were included. Complete obliteration was achieved in 91.6% of patients with 100% technical success. Mean number of deployed coils and volume of injected CYA glue were 1.16 and 1.58 mL, respectively.Conclusions EUS-guided angiotherapy is an effective and safe intervention for managing GV bleeding with high technical success rate.
Keywords: gastric varices; coil; cyanoacrylate glue and EUS